The Influence of Different Size of Filler in Peat Consolidation Study - Nik Azran, Nik Abdul Muhaimin; Nik Azman, Nik Ahmad Hakim; Mohd Razali, Siti Nooraiin (Multidisciplinary Applied Research and Innovation, 2024)
The introduction provides an overview of the importance of peat soil and its use in engineering projects. The paper discusses the characteristics of peat soil, including its properties that make it unsuitable for use as a foundation for infrastructure projects as well as its importance to the environment. The study then outlines the purpose of the study, which is to understand the settlement behaviours of peat in its original state and the influence of different sizes of sand as fillers on the consolidation of peat. The scope of the study is then outlined, including the sample location, the types of tests that will be conducted, and the expected outcomes. Finally, the paper presents the objectives and problem statement of the study, which aim to determine the settlement behaviour of peat soil and understand the influence of various sizes of filler in consolidation studies. This provides a clear and concise overview of the content of the study, including its purpose, background, objectives, scope, and future outcomes. Overall, this introduction provides a solid foundation for the paper and sets the stage for the reader to understand the importance and relevance of the study.